From history to up-to-date realities of organ transplantation in Russia - A. V. Chzhao (Трансплантология (Москва), 2016)
The paper describes the problems of transplantation in Russia. Pages of history, the concept of brain death, fundamental principles of post-mortem organ donation have been analyzed. The emphasis is made on the need for opening of Chairs of Transplantation in medical educational institutions, broad involvement of the media, as well as administrative resources for the development of organ donation in the country.